THE RELATIONSHIP BETWEEN THE CATEGORIES OF EMOTIONALITY AND EXPRESSIVITY IN ENGLISH AND UZBEK LANGUAGES - Bakhramova Zamira Rahimovna (Bright Mind Publishing, 2025)
The English and Uzbek languages, based on their large lexical and grammatical systems, express emotionality and expressiveness in their own way. This article studies the definition of the categories of emotionality and expressiveness in the English and Uzbek languages, their ways of expression in the language, and their similarities and differences.
Keywords: English, Uzbek, emotionality, emotionality, lexis, semantics, words.